DIGITAL PLATFORMS AS A CATALYST FOR EFFECTIVE PROJECT MANAGEMENT IN LOCAL COMMUNITIES - POLIKROVSKII, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the context of decentralization and digital transformation, territorial communities of Ukraine are increasingly actively implementing digital platforms to simplify their management processes. The purpose of the study is to practically substantiate the possibilities of using digital platforms in project management of territorial communities of Ukraine in conditions of war and martial law in the country. Universal methods of scientific knowledge were used in the research process. The study used methods of system analysis, case method, comparative analysis of foreign and domestic experience, as well as logical generalization to determine the effects of digital tools at all stages of the project cycle. A comprehensive review of digital platforms used in project management of territorial communities was carried out. The functional capabilities of universal tools were analyzed. Separately, specialized platforms created for e-democracy and financial transparency were studied, among which e-DEM (petitions, participatory budgeting, public discussions), Prozorro (e-procurement), "Diya" (public services portal), as well as open budget and public finance portals occupy a key place. A qualitative comparison of Ukrainian digital solutions with the experience of Poland and Estonia was also carried out. It was found that Ukraine has achieved significant progress in the implementation of unified national platforms in a short period of time, in particular Prozorro and "Diya", which provide centralized access to public services and are comparable to Polish and Estonian analogues. The Polish experience showed consistency in the development of public budgets and participation, while Estonia became a model of digital integration of registers and e-government. Based on the study, the key functional capabilities of digital platforms were systematized in terms of project cycle stages. It was determined that digital tools contribute to ensuring transparency through open data (Prozorro, budgets), efficiency - through automation of procedures and remote management (Diya), public participation - through electronic consultations, voting and participatory budgets (e-DEM), as well as control - through feedback mechanisms, online monitoring of project implementation and access to reporting. The conclusions emphasize that digital platforms play the role of an institutional framework for forming a culture of accountability, interaction and innovative development in the local government system.